Carrot-based fermentation juice rich in sleep-promoting components improved sleep in mice - Liu, Daiyao; Zhang, Jianming; Chen, Juan; Zhang, Chengcheng; Yi, Huaxi; Liu, Daqun (Frontiers in Nutrition, 2022)
The impact of fermentation by Levilactobacillus brevis YSJ3 on sleep-promoting components (SPCs) of carrot juice was evaluated. The contents of acetic acid, isovaleric acid, butyric acid, and γ-aminobutyric acid (GABA) significantly increased after fermentation. The beneficial effects of fermented carrot juice (FCJ) on sleep were evaluated in animal experiments. Behavioral test reveal SPCs-enriched FCJ could effectively relieve anxiety. The sleep duration in the FCJ group were extended compared to the control (NC) group and the unfermented carrot juice (UCJ) group. Moreover, the relative abundances of Ruminiclostridium and Akkermansia in the FCJ group and PC group, respectively, increased significantly, compared to the NC group the UCJ group. The contents of gut short-chain fatty acids in the FCJ group were significantly higher than that in the NC group and the UCJ group. The levels of GABA and 5-hydroxytryptamine in the brain for the FCJ group also increased significantly, compared to the NC group and the UCJ group. It indicated that SPCs-enriched FCJ effectively improved sleep in mice, which might be related to the fermentation of carrot juice and the compounds produced during the fermentation.